Unmaking Migrants : Nigeria's Campaign to End Human Trafficking - Vanderhurst, Stacey (Book collections on Project MUSE., 2022)
"An ethnographic account of Nigeria's campaign to stop human trafficking and migration into sex work, told from inside a rehabilitation center for trafficked women" --